THE EFFECT OF PH VARIATIONS ON THE STRUCTURE OF THE MnFe2O4/PS NANOCOMPOSITE LAYER AS SELF CLEANING - Ipal Ipal; - Ratnawulan (Department of Physics – Universitas Negeri Padang UNP, 2021)
Manganese is a metal element found in group VII, has an atomic weight of 54.93u, with a boiling point of 20320˚C, while the melting point is 12470˚C, and has a reddish-gray color. Iron (III) oxide (Fe2O3) or also known as hematite or maghemite iron ore, iron hematite (α – Fe2O3) is a simple oxide which has a hexagonal (rhombohedral) structure and has the R3c space group. Manganese was used as reinforcement in this research, while the matrix used was polystyrene. In this study, 5 variations of pH MnFe2O4/PS, namely 5,6,7,8 and 9 nanocomposites were synthesized using the spin coating method with manganese oxide (MnO2) and iron ore (Fe2O3) precursors. The composite gel is dropped on the glass substrate then the drying process is carried out in an oven. MnFe2O4/PS nanocomposites were characterized using X-Ray Diffraction (XRD). giving acid and alkaline solutions affects the size of the crystals, when adding a base (25% Na4OH) the crystal size becomes small while when the acid is added (100% CO3COOH) the crystal size is larger. : pH 8: pH 9 an increase in crystal size and grain size occurs.